A facile approach to fabricate free-standing hydrogen evolution electrodes: riveting tungsten carbide nanocrystals to graphite felt fabrics by carbon nanosheets. Issue 16 (6th April 2016) - Shen, Yi; Li, Ling; Xi, Jingyu; Qiu, Xinping
Abstract : We report a novel three-dimensional architecture, consisting of tungsten carbide nanocrystals which are intimately riveted to graphite felt fabrics by carbon nanosheets (CNS@WC/GF). Abstract : We report a novel three-dimensional architecture, consisting of tungsten carbide nanocrystals which are intimately riveted to graphite felt fabrics by carbon nanosheets (CNS@WC/GF). The as-prepared CNS@WC/GF monolith is utilized as a binder-free hydrogen evolution reaction electrode in both acidic and alkaline solutions. It demonstrates remarkable activity as well as durability.